Night drive - Sala, Richard; Burbey, Mark (Fantagraphics Books Inc., 2024)
"When Richard Sala passed away in 2020, he left behind a uniquely eldritch body of graphic novels and illustrations, fueled by macabre whimsy and a love of dark mysteries and vintage monsters. Like David Lynch, Sala was a painter who turned to a storytelling medium that allowed him to create inventive narratives inspired by such disparate influences as French crime fiction, the grim humor of Charles Addams, the surreal poetry of Jorge Luis Borges, and his own penchant for all things gleefully ghoulish and sinister."--